Inducible cytochrome P450 activities in renal glomerular mesangial cells: biochemical basis for antagonistic interactions among nephrocarcinogenic polycyclic aromatic hydrocarbons - Falahatpisheh, MH (BioMed Central, 2004)
BACKGROUND: Benzo(a)pyrene (BaP), anthracene (ANTH) and chrysene (CHRY) are polynuclear aromatic hydrocarbons (PAHs) implicated in renal toxicity and carcinogenesis. These PAHs elicit cell type-specific effects that help predict toxicity outcomes in vitro and in vivo. While BaP and ANTH selectively injure glomerular mesangial cells, and CHRY targets cortico-tubular epithelial cells, binary or ternary mixtures of these hydrocarbons markedly reduce the overall cytotoxic potential of individual hydrocarbons. METHODS: To study the biochemical basis of these antagonistic interactions, renal glomerular mesangial cells were challenged with BaP alone (0.03 – 30 μM) or in the presence of ANTH (3 μM) or CHRY (3 μM) for 24 hr. Total RNA and protein will be harvested for Northern analysis and measurements of aryl hydrocarbon hydroxylase (AHH) and ethoxyresorufin-O-deethylase (EROD) activity, respectively, to evaluate cytochrome P450 mRNA and protein inducibility. Cellular hydrocarbon uptake and metabolic profiles of PAHs were analyzed by high performance liquid chromatography (HPLC). RESULTS: Combined hydrocarbon treatments did not influence the cellular uptake of individual hydrocarbons. ANTH or CHRY strongly repressed BaP-inducible cytochrome P450 mRNA and protein expression, and markedly inhibited oxidative BaP metabolism. CONCLUSION: These findings indicate that antagonistic interactions among nephrocarcinogenic PAHs involve altered expression of cytochrome P450s that modulate bioactivation profiles and nephrotoxic/ nephrocarcinogenic potential.